Predictors of acute kidney injury in patients with acute decompensated heart failure in emergency departments in China. Issue 9 (September 2021) - Ge, Hongxia; Liang, Yang; Fang, Yingying; Jin, Yi; Su, Wenting; Zhang, Guoqiang; Wang, Jing; Xiong, Hui; Shang, Deya; Chai, Yanfen; Liu, Zhi; Wei, Hongyan; et al.
Objective: This retrospective multicentre observational study was performed to assess the predictors of acute kidney injury (AKI) in patients with acute decompensated heart failure (ADHF) in emergency departments in China. Methods: In total, 1743 consecutive patients with ADHF were recruited from August 2017 to January 2018. Clinical characteristics and outcomes were compared between patients with and without AKI. Predictors of AKI occurrence and underdiagnosis were assessed in multivariate regression analyses. Results: Of the 1743 patients, 593 (34.0%) had AKI. AKI was partly associated with short-term all-cause mortality and cost. Cardiovascular comorbidities such as coronary heart disease, diabetes mellitus, and hypertension remained significant predictors of AKI in the univariate analysis. AKI was significantly more likely to occur in patients with a lower arterial pH, lower albumin concentration, higher creatinine concentration, and higher N-terminal pro-brain natriuretic peptide (NT-proBNP) concentration. Patients treated with inotropic agents were significantly more likely to develop AKI during their hospital stay. Conclusion: This study suggests that cardiovascular comorbidities, arterial pH, the albumin concentration, the creatinine concentration, the NT-proBNP concentration, and use of inotropic agents are predictors of AKI in patients with ADHF.